2018 IEEE/ACM International Conference on Advances in Social Networks Analysis and Mining (ASONAM) 2018
DOI: 10.1109/asonam.2018.8508776
|View full text |Cite
|
Sign up to set email alerts
|

Of Wines and Reviews: Measuring and Modeling the Vivino Wine Social Network

Abstract: This paper presents an analysis of social experiences around wine consumption through the lens of Vivino, a social network for wine enthusiasts with over 26 million users worldwide. We compare users' perceptions of various wine types and regional styles across both New and Old World wines, examining them across price ranges, vintages, regions, varietals, and blends. Among other things, we find that ratings provided by Vivino users are not biased by cost. We then study how wine characteristics, language in wine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Kotonya et al . () analysed the content and construction Vivino ratings and found that community comments and ratings express similar rich knowledge of wines as experts, wines are typically assessed within geographical regions and the analysis of website usage points to the absence of spam and/or trolls affecting the credibility of the ratings. This evidence points to some credibility for the community ratings data employed.…”
Section: Data and Empirical Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Kotonya et al . () analysed the content and construction Vivino ratings and found that community comments and ratings express similar rich knowledge of wines as experts, wines are typically assessed within geographical regions and the analysis of website usage points to the absence of spam and/or trolls affecting the credibility of the ratings. This evidence points to some credibility for the community ratings data employed.…”
Section: Data and Empirical Specificationmentioning
confidence: 99%
“…Vivino (https://www.vivino.com/wine-news/vivino-5-star-rating-system) claim credibility of their community ratings pointing to strong correlations between their community ratings and a number of wine experts and also suggest they are not influenced by advertising or sponsorship. Kotonya et al (2018) analysed the content and construction Vivino ratings and found that community comments and ratings express similar rich knowledge of wines as experts, wines are typically assessed within geographical regions and the analysis of website usage points to the absence of spam and/or trolls affecting the credibility of the ratings. This evidence points to some credibility for the community ratings data employed.…”
Section: Data and Empirical Specificationmentioning
confidence: 99%
“…In contrast, the study by Kotonya (2018) gives little evidence for a strong relationship between prices and consumer ratings. Nevertheless, both Kotonya’s (2018) and Oczkowski and Pawsey’s (2019) results suggest that expert opinions and online wine community reviews are related and often comparable. Such results have also been confirmed by a recent market experiment run by U.S. wine critic Ester Mobley on Vivino users from California in 2022.…”
Section: Introductionmentioning
confidence: 89%
“…Multiple studies support this claim (Oczkowski and Doucouliagos, 2015; Schamel and Anderson, 2003; Schamel and Ros, 2021), at least for high-rated “superstar” wines (Castriota et al, 2022). Demand for highly rated wines among wine producers has increased, causing an inflation of prices (Kotonya et al, 2018). Considering this, significant scrutiny has arisen regarding the validity of expert wine ratings as sensory evaluations are profoundly subjective, reflecting the taste preferences of just one individual (Oczkowski and Pawsey, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on recommendation systems show that some researchers have analyzed some shared data from commercial platforms for wine and online games. The analysis of the SNS data from 9.2 million wine brands and 29.9 million reviews showed the tendency of user preference of wine in terms of the origin and age of the wine [7,8]. Although the tendency of user preference is useful for designing user models in practical recommendation systems, user behavior affecting the commercial effectiveness of the recommendation system remains unclarified.…”
Section: Introductionmentioning
confidence: 99%